FINANCIAL INCLUSION AND THE ROLE OF BANKS IN EXPANDING ACCESS TO FINANCIAL SERVICES - Hakimboy, Rojabov; Gautama, Budhi Pamungkas; Hendrayati, Heny; Qudratov, Inomjon (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Financial inclusion has become a central development priority because it links household welfare, enterprise growth, resilience, digital transformation, and long-term social inclusion. This article examines financial inclusion through the specific lens of the banking sector and analyses how banks expand access to payments, savings, credit, insurance, and digital financial services for underserved populations. Using a structured literature review, the paper synthesises scholarship on financial access, bank outreach, branch expansion, agent banking, mobile banking, digital onboarding, consumer protection, and small business finance, with particular attention to Uzbekistan. The review shows that banks remain pivotal institutions because they combine deposit mobilisation, risk management, regulatory accountability, payment infrastructure, and the ability to intermediate funds at scale. At the same time, access alone is not sufficient. Sustainable inclusion depends on affordability, service quality, trust, financial capability, gender-sensitive product design, last-mile delivery channels, and user protection. The article concludes that banks are most effective when they move beyond traditional branch-centred models and integrate digital channels, simplified products, data-informed credit assessment, partnerships with non-bank providers, and targeted strategies for women, youth, rural households, migrants, and MSMEs. For Uzbekistan, the next stage of financial inclusion will depend on stronger digital payments usage, broader savings mobilisation, reduced exclusion in MSME finance, and more relevant formal financial services in everyday economic life.